A closed-loop brain computer interface for real-time seizure detection and control - Liang, Sheng-Fu; Shaw, Fu-Zen; Young, Chung-Ping; Chang, Da-Wei; Liao, Yi-Cheng (2010 Annual International Conference of the IEEE Engineering in Medicine and Biology, 2010)
The worldwide prevalence of epilepsy is approximately 1%, and 25% of epilepsy patients cannot be treated sufficiently by available therapies. Brain stimulation with closed-loop seizure control has recently been proposed as an innovative and effective alternative. In this paper, a portable closed-loop brain computer interface for seizure control was developed and shown with several aspects of advantages, including high seizure detection rate (92-99% during wake-sleep states), low false detection rate (1.2-2.5%), and small size. The seizure detection and electrical stimulation latency was not greater than 0.6 s after seizure onset. A wireless communication feature also provided flexibility for subjects freeing from the hassle of wires. Experimental data from freely moving rats supported the functional possibility of a real-time closed-loop seizure controller.